2015
DOI: 10.5430/wje.v5n1p25
|View full text |Cite
|
Sign up to set email alerts
|

Economic Literacy Levels of Social Studies Teacher Candidates

Abstract: The purpose of this study is to determine the levels of economic literacy -an important component of being a good citizen -among seniors studying at social studies teacher program which aims at cultivating good citizens and to find out its relationships in terms of various variables. The quantitative sample of the study was comprised of 726 senior teacher candidates studying at Social Studies Teacher Education Program of the universities from seven different regions in 2013-2014 academic year. The qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 16 publications
6
14
0
5
Order By: Relevance
“…Furthermore, most in-service training programs focus on teaching methods, building assessments tools, and educational technology. The current results can be said to be similar to some of the previous studies conducted on the economic literacy of teachers (Akhan, 2015;Al-Rabaani & Al-Mikhlafi, 2011;Fagan, 2007;Hindi, 1998). The current and previous studies raised the issue of teaching economic literacy in schools in general and Oman in particular where the economic literacy of social studies need to be enhanced to ensure that teachers can make a significant difference with their students.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, most in-service training programs focus on teaching methods, building assessments tools, and educational technology. The current results can be said to be similar to some of the previous studies conducted on the economic literacy of teachers (Akhan, 2015;Al-Rabaani & Al-Mikhlafi, 2011;Fagan, 2007;Hindi, 1998). The current and previous studies raised the issue of teaching economic literacy in schools in general and Oman in particular where the economic literacy of social studies need to be enhanced to ensure that teachers can make a significant difference with their students.…”
Section: Discussionsupporting
confidence: 91%
“…The results also revealed that there are gender differences in teachers' level of economic literacy, with females having a higher level of literacy about countries of highest national and individual income, while male teachers showed a higher level of knowledge about monetary policies, corroborating previous studies (Akhan, 2015;Grimes, Millea, & Thomas, 2007;Yohanes et al, 2017). Such differences could be attributed to gender-related background and field of interest.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations